Urinary iodine excretion in healthy Mexican adults - Armando Flores-Rebollar; Marisol Lendechy Velázquez; Andrea Castro Sánchez; Guadalupe López Carrasco; Aída Ruiz Juvera (Archivos Latinoamericanos de Nutrición)
The iodine nutritional status of a population is mainly measured by urinary iodine excretion (UI) and thyroid volume determined by ultrasound (US). The surveillance of nutritional iodine levels in the Mexican population has been insufficient. Our aim was to determine the UI in random samples from adults living in an urban area. We selected a sample of healthy individuals over the age of 18 that were students, physicians or administrative personnel at our Institution and had no known thyroid disease. Thyroid volume was determined by ultrasound in all volunteers as well as thyroid hormones and antithyroid antibodies and a urine sample was obtained. One hundred and two volunteers with a median age of 29, participated in the study. The group’s median UI was 221 μg/L,interquartile range (IQR)(135.0 to 356.8) and no differences were observed between genders: women had a UI of 218.0 μg/L IQR (129.0 a 351.0) vs. 223.0 μg/L IQR (138.0 to 374.0) in males, p 0.941. Excessive dietary iodine intake was established in 31.4% of all volunteers according to their UI, placing them at risk of thyroid dysfunction. It is fundamental to evaluate the national iodine nutritional status in Mexico. We discuss the current status of the nutritional state in the Americas, emphasizing that in Latin America and the observed tendency in the region to ingest a diet high in iodine.